The Typology of Irregular Plural in the Qur’an: A Morphosyntactical Study of Ultimate Plural - Ma’rifah Munjiah; Kisno Umbar; Sinta Nuriyah SR (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This research aims to identify the quantity, pattern, and characteristics of the irregular plural forms in Arabic, especially shighah muntaha al-jumu’ (ultimate plural) in the Qur'an. This research was conducted based on the many problems in identifying the pattern of ultimate plural. Although most of them are analogous, students still complain that it is complex, and as a solution they memorize. However, it still raises its own problems because of the many patterns. The study implemented a text study approach supported by data cards as a data collection instrument. The researchers managed to identify ultimate plural with a variety of patterns. This study found 245 ultimate plurals in the Quran. From these findings, researchers successfully found twelve (12) patterns of ultimate plural in the Quran. This finding certainly simplifies the nineteen (19) patterns of ultimate plural which Arabic language experts often introduce. The characteristics of ultimate plural can be identified from its singular form, which consists of words with at least four letters and the second letter is not a vowel. Meanwhile, when it comes to plural, the third letter is alif taksir followed by two or three letters. The patterns can be formulated in A-A/I, U-A/I, U-A/A and A-A/A.